Dynamics of coupled structures. proceedings of the 36th IMAC, a Conference and Exposition on Structural Dynamics 2018 /: proceedings of the 36th IMAC, a Conference and Exposition on Structural Dynamics 2018. Volume 4 : (2018) - Unknown
No abstract available